AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN JARAK MERAH (Jatropha gossypiifolia) ASAL KABUPATEN BANTAENG - Wahyuddin, Nurzadrina; Ismail, Ismail; Mashar, Harlyanti Muthma'innah; Dali (Jurnal Kefarmasian Akfarindo, 2022)
Background: In the last few decades there has been an increase in cases of chronic diseases and premature aging which are some of the key factors in influencing public health. This condition is caused by various causes, but the main factor is the number of free radicals that exceed the body's capacity to neutralize them. Antioxidants have an important role as health protective factors because they can neutralize and protect cells from the presence of free radicals. Red castor leaves have been reported to have good activity as an antioxidant. The chemical content of this plant is anthraquinone, flavonoid, saponin, tannin and terpenoid. Objective: This study aimed to evaluate the antioxidant activity of red jatropha leaf extract using the DPPH method. Methods Samples were extracted using 70% ethanol by maceration method. The antioxidant activity test was carried out using the DPPH method (1,1-diphenyl-2-picrylhydrazyl) using a comparison of Vitamin C. Each test used a variation of the concentration of the solution. For red jatropha leaf extract using concentration variations of 20, 40, 60, 80 and 100 g/ml, while for vitamin C using concentration variations of 10, 15, 20, 25, and 30 g/ml. The absorbance of each test solution was measured using a spectrophotometer at a wavelength of 515 nm. The results are reported as IC50 values. Results: The results showed that the IC50 values ​​of red jatropha leaf extract and vitamin C were 47.81 and 14.99 g/ml, respectively. This value indicates that the Chinese jatropha leaf extract has a very strong antioxidant activity (IC50 <50 g/ml). Conclusion: Red jatropha leaf extract showed very strong antioxidant activity with an IC50 value of 47.81 g/ml so it has great potential as an antioxidant that can be used for the development of traditional medicinal raw materials.